2005
DOI: 10.1080/02607470500043771
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a lecturer in further education in England: the construction of professional identity and the role of communities of practice

Abstract: Further education colleges in England, which offer a wide range of post-school education and training provision, have undergone major transformations in the past decade, resulting in considerable changes to the work of those involved in teaching in colleges. This paper examines the development of professional identity, as a means of exploring how cultures of learning and teaching are developing and changing in the sector. The paper considers the formation of professional identity amongst a group of trainee lec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(81 citation statements)
references
References 11 publications
2
79
0
Order By: Relevance
“…Their concepts have been used to understand how trainee teachers can learn from more experienced teachers (Bathmaker & Avis, 2005;Drever & Cope, 1999), and how people in the workplace are able to learn from their colleagues through the establishment of communities of practice (Brown & Duguid, 1991;Kimble, Hildreth & Wright, 2001). Furthermore, their theories have been used to understand how intercultural learning arose out of collaborative European Union research projects (Somekh & Pearson, 2002) and how PhD students found emotional and academic support through a collaborative peer community (Janson, Howard & Schoenberger-Orgad, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Their concepts have been used to understand how trainee teachers can learn from more experienced teachers (Bathmaker & Avis, 2005;Drever & Cope, 1999), and how people in the workplace are able to learn from their colleagues through the establishment of communities of practice (Brown & Duguid, 1991;Kimble, Hildreth & Wright, 2001). Furthermore, their theories have been used to understand how intercultural learning arose out of collaborative European Union research projects (Somekh & Pearson, 2002) and how PhD students found emotional and academic support through a collaborative peer community (Janson, Howard & Schoenberger-Orgad, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of this, according to Crowley (2002), leads teachers to work in isolation. Second, as Bathmaker and Avis (2005) found, these changes impact negatively on teachers who are demoralized and overstretched. Edward et al (2007) report that teachers and managers described coping with endless change coming at them from all directions and struggling to balance the needs of their learners with the demands of their managers, inspectors, and funding sources.…”
Section: Structural Barriers To Meaningful Professional Developmentmentioning
confidence: 90%
“…This isolation limited trainees' opportunities to develop affective relationships and access feedback. Like LSS trainees in other studies (Bathmaker and Avis, 2005;Maxwell, (forthcoming), case study trainees had limited opportunity to access teacher communities of practice, so were denied access to an important affordance that could have supported them in developing subject knowledge and pedagogy (Bank, Leech & Moon, 1999). …”
Section: Workplace Affordances For Learningmentioning
confidence: 99%